2014
DOI: 10.1016/j.bjhh.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Study of enzyme replacement therapy for Gaucher Disease: comparative analysis of clinical and laboratory parameters at diagnosis and after two, five and ten years of treatment

Abstract: ObjectiveTo evaluate the impact of enzyme replacement therapy for Gaucher Disease on clinical and laboratory parameters after two, five and ten years of treatment.MethodsData were collected from patient records and analyzed using BioEstat software (version 5.0). Student's t-test, Analysis of Variance (ANOVA), Wilcoxon test and Kruskal–Wallis test were used for statistical analysis. Hepatomegaly and splenomegaly were analyzed using the Kappa test.ResultsThere was a significant increase in hemoglobin levels (p-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(34 reference statements)
1
3
0
2
Order By: Relevance
“…This data corroborates a study that evaluated the impact of enzyme therapy for patients with Gaucher disease in clinical and laboratory parameters after two, five and ten years of treatment, where 61.5% of the sample was female (8) . Similarly, the Gaucher Register of the International Collaborative Gaucher Group (ICGG) -a multicenter registry with demographic and clinical results, created in 1991 -showed that in Brazil, out of a total of 551 registered and accompanied patients, 58% were female, closely matching world data (53%) (9) .…”
Section: Discussionsupporting
confidence: 88%
“…This data corroborates a study that evaluated the impact of enzyme therapy for patients with Gaucher disease in clinical and laboratory parameters after two, five and ten years of treatment, where 61.5% of the sample was female (8) . Similarly, the Gaucher Register of the International Collaborative Gaucher Group (ICGG) -a multicenter registry with demographic and clinical results, created in 1991 -showed that in Brazil, out of a total of 551 registered and accompanied patients, 58% were female, closely matching world data (53%) (9) .…”
Section: Discussionsupporting
confidence: 88%
“…The duration of the treatment ranged from 0.17 to 20 years, with a mean of 6.07 (±6.37) years. This was implemented in line with the international recommendations 28,29. Adverse events from ERT were detected in 3.2% of our population.…”
Section: Discussionmentioning
confidence: 74%
“…La EG tipo 3 es de presentación más tardía y progresión más lenta (42). La mayoría de los pacientes llegan a la adultez, en promedio hasta la tercera década de la vida (34,52).…”
Section: Pronósticounclassified